Surgical treatment outcome on a national cohort of 176 patients with cervical manifestation of rheumatoid arthritis - Macdowall, Anna; Barany, Laszlo; Bodon, Gergely (Journal of Craniovertebral Junction and Spine, 2021)
Purpose: Rheumatoid arthritis (RA) affecting the cervical spine results in instability and deformity that can be divided into the subtypes C1-C2 horizontal (atlantoaxial instability), C0-C2 vertical (basilar invagination), subaxial, and combined instabilities. The aim of this study was to compare the surgical treatments and outcomes of RA-related deformity and instability in a population-based setting.
CRIS-Team WoS Importer:2022-02-25